Pengaruh Model Pembelajaran Numbered Head Together (NHT) Terhadap Keaktifan dan Hasil Belajar Siswa Akuntansi di SMK Negeri 5 Palembang - Wulandari, Ika; Gunawan, Hendri; Aradea, Riswan (LPPM Institut Pendidikan Nusantara Global, 2024)
Numbered Head Together means students participate in 4 to 5 discussion groups. Each group is given a number so that students become more active in expressing opinions, asking and answering questions. The aim of this research is to determine the effect of the numbered head together learning model on student activity and learning outcomes at SMK Negeri 5 Palembang. This research uses experimental research, the method used is Quasi Experimental Design with the Nonequivalent Control Group Design type. The sample used was saturated sampling in class X AKL 1, totaling 29 students and X AKL 2, totaling 30 students. This research carried out hypothesis testing using the t test, namely the independent sample t test. Based on the research results, the t_(calculation) value is greater than t_(table) (3.451 > 1.705), so it can be interpreted that the NHT learning model has an effect on activity and the t_(calculation) value is greater than t_(table) (3.317 > 1.705 ), then it can be interpreted that the NHT learning model influences student learning outcomes in accounting subjects.